Purification and Preliminary Characterization of Biopigments From Nitzschia closterium - Hasti Asfarina; Dayu Wiyanti Purnaningtyas (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Biopigments are important bio-based compounds used in food, pharmaceutical, and cosmetic industries. Nitzschia closterium, a marine diatom microalga, is known for its potential to produce various pigments. This study aimed to purify and preliminarily characterize biopigments extracted from Nitzschia closterium. The research involved microalgal biomass cultivation, harvesting, pigment extraction, preliminary identification using thin-layer chromatography (TLC), and purification through column chromatography. After six days of cultivation, the average biomass density reached 1.67 g/L. TLC analysis of the crude pigment extract showed nine distinct pigment bands. Chromatographic purification and comparison with the TLC profile indicated four major pigment groups. Fractions 16 and 17 were predicted to be β-carotene (band 9); fractions 18 and 19 likely represented pheophytins (band 8); fractions 20 to 30 contained chlorophylls and their derivatives (bands 5–7); and fractions 31 to 45 showed orange-yellow hues associated with xanthophyll-type carotenoids (bands 2–4). These results demonstrate that Nitzschia closterium is a promising natural source of multiple biopigments, and that TLC and column chromatography effectively supported their purification and initial characterization.